2000
DOI: 10.1164/ajrccm.162.4.9909120
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Polymorphisms in the Angiotensin Converting Enzyme Gene Are Associated with Pulmonary Hypertension Evoked by Exercise Challenge in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Angiotensin converting enzyme (ACE) plays an important role in the pathogenesis of pulmonary hypertension. In this study we determined whether the deletion (D)/insertion (I) polymorphism in the ACE gene may be associated with pulmonary hypertension evoked by exercise challenge in patients with chronic obstructive pulmonary disease (COPD). ACE genotypes were determined in 19 patients with COPD. All patients underwent right heart catheterization followed by a constant-load exercise test while breathing room air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 17 publications
5
66
1
3
Order By: Relevance
“…To address this hypothesis, it is important that future studies undertake the assessment of both muscle strength and endurance in combination with muscle biopsy analysis of fiber types (Harry et al, 2004). Kanazawa et al (2000) suggested that the I/D polymorphism in the ACE gene may be associated with pulmonary hypertension evoked by exercise challenge in patients with COPD. Similarly, Tkacova et al (2005) noted that increases in pulmonary artery pressure in patients with COPD are related to the ACE I/D polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…To address this hypothesis, it is important that future studies undertake the assessment of both muscle strength and endurance in combination with muscle biopsy analysis of fiber types (Harry et al, 2004). Kanazawa et al (2000) suggested that the I/D polymorphism in the ACE gene may be associated with pulmonary hypertension evoked by exercise challenge in patients with COPD. Similarly, Tkacova et al (2005) noted that increases in pulmonary artery pressure in patients with COPD are related to the ACE I/D polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association between ACE activity and OSAHS (Rohatgi, 1982;Kanazawa et al, 2000;Barcelo et al, 2001) but the results are inconsistent. A correlation between homozygous gene deletion (DD genotype) and high ACE activity has been reported in many studies (Ozen et al, 1997;Seckin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40] Some, but not all, of these studies emanate from clinical trials of exercise, diet or drug treatment interventions on blood pressure regulation. The most widely studied gene in this context is the angiotensinogen I-converting enzyme gene (ACE).…”
Section: Gene-environment Interactionmentioning
confidence: 99%
“…Studies examining the modifying roles of ACE genotypes on blood pressure response to exercise have focused primarily on the effects of acute exercise often in relatively small samples. [32][33][34][35][36][37][38][39] At least two medium-to long-term clinical trials from North America 37 and Finland 40 have reported on the association between ACE genotypes and blood pressure responses to long-term aerobic exercise training. In the North American HERITAGE study, Rankinen and colleagues examined the blood pressure response by ACE I/D and M235T genotypes to an exercise stress test before and after 20 weeks of aerobic exercise training.…”
Section: Gene-environment Interactionmentioning
confidence: 99%